Privacy enhanced matrix factorization for recommendation with local differential privacy - Shin, Hyejin (2018)
Recommender systems are collecting and analyzing user data to provide better user experience. However, several privacy concerns have been raised when a recommender knows user's set of items or their ratings. A number of solutions have been suggested to improve privacy of legacy recommender systems, but the existing solutions in the literature can protect either items or ratings only. In this paper, we propose a recommender system that protects both user's items and ratings. We develop novel matrix factorization algorithms under local differential privacy (LDP). In a recommender system with LDP, individual users randomize their data themselves to satisfy differential privacy and send the perturbed data to the recommender. Then, the recommender computes aggregates of the perturbed data. This framework ensures that both user's items and ratings remain private from the recommender. However, applying LDP to matrix factorization typically raises utility issues with high dimensionality and iterative algorithms. To tackle these technical challenges, we adopt dimensionality reduction technique and a sampling-based binary mechanism. We introduce a factor that stabilizes the perturbed gradients. With MovieLens and LibimSeTi datasets, we evaluate accuracy of our recommender system and demonstrate that our algorithm performs better than the existing differentially private gradient descent algorithm for matrix factorization under stronger privacy requirements.